Modeling the fate and end-of-life phase of engineered nanomaterials in the Japanese construction sector. (February 2018) - Suzuki, Shinya; Part, Florian; Matsufuji, Yasushi; Huber-Humer, Marion
Graphical abstract: Highlights: First dynamic flow model for engineered nanomaterials and nanowastes in Japan. Nano-TiO2, -SiO2, -Al2 O3 and carbon black are used for construction materials. About 4029 to 4785 tons of ENMs are annually produced for the construction sector. In 2016, about 95% of the used ENMs remained in buildings and roads. In 2016, about 5% of the used ENMs reached their end of useful life. Abstract: To date construction materials that contain engineered nanomaterials (ENMs) are available at the markets, but at the same time very little is known about their environmental fate. Therefore, this study aimed at modeling the potential fate of ENMs by using the example of the Japanese construction sector and by conducting a dynamic material flow analysis. Expert interviews and national reports revealed that about 3920–4660 tons of ENMs are annually used for construction materials in Japan. Nanoscale TiO2, SiO2, Al2 O3 and carbon black have already been applied for decades to wall paints, road markings or concrete. The dynamic material flow model indicates that in 2016 about 95% of ENMs, which have been used since their year of market penetration, remained in buildings, whereas only 5% ended up in the Japanese waste management system or were diffusely released into the environment. Considering the current Japanese waste management system, ENMs were predicted to end up in recycled materials (40–47%) or in landfills (36–41%). It was estimated that only a small proportion was used in agriculture (5–7%, as ENM-containing sewage sludges) or was diffusely released into soils, surface waters or the atmosphere (5–19%). The results indicate that ENM release predominantly depend on their specific applications and characteristics. The model also highlights the importance of adequate collection and treatment of ENM-containing wastes. In future, similar dynamic flow models for other countries should consider, inasmuch as available, historical data on ENM production (e.g. like declaration reports that are annually published by relevant public authorities or associations), as such input data is very important regarding data reliability in order to decrease uncertainties and to continuously improve model accuracy. In addition, more environmental monitoring studies that aim at the quantification of ENM release and inadvertent transfer, particularly triggered by waste treatment processes, would be needed in order to validate such models.